A humanized mouse model for in vivo evaluation of invariant Natural Killer T cell responses - Saavedra-Avila, Noemi Alejandra; Dellabona, Paolo; Casorati, Giulia; Veerapen, Natacha; Besra, Gurdyal S.; Howell, Amy R.; Porcelli, Steven A. (Frontiers in Immunology, 2022)
Invariant natural killer T (iNKT) cells mediate immune responses when stimulated by glycolipid agonists presented by CD1d. In extensive studies of synthetic analogues of α-galactosyl ceramides, we identified numerous examples of significant differences in the recognition of specific glycolipids in wild type mice versus human iNKT cell clones or PBMC samples. To predict human iNKT cell responses more accurately in a mouse model, we derived a mouse line in which compound genetic modifications were used to express a human-like iNKT cell TCR along with human CD1d in place of the endogenous mouse proteins. Detailed transcriptional and phenotypic profiling demonstrated that these partially humanized mice developed an expanded population of T cells recognizing CD1d-presented glycolipid antigens, among which a subset characterized by expression of chemokine receptor CXCR6 had features characteristic of authentic iNKT cells. Responses to iNKT cell activating glycolipids in these mice generated cytokine production in vitro and in vivo that showed a pattern of fine specificity that closely resembled that of cultured human iNKT cell clones. Anti-tumor responses to variants of α galactosyl ceramide in VαKI mice also correlated with their potency for stimulating human iNKT cells. This genetically modified mouse line provides a practical model for human presentation and recognition of iNKT cell activators in the context of a normally functioning immune system, and may furnish valuable opportunities for preclinical evaluation of iNKT cell-based therapies.